Primary reverse shoulder arthroplasty for acute proximal humerus fractures: A 5-year long term retrospective study of elderly patients. Issue 11 (November 2019) - Luciani, Pierfrancesco; Farinelli, L.; Procaccini, R.; Verducci, C.; Gigante, A.
Highlights: Reverse shoulder arthroplasty (RSA) in complex shoulder fractures is even more frequently. The consolidation of tuberosities in anatomic consolidation determined more satisfied results in terms of pain, disability and range of motion. RSA represent a valid option of treatment for complex proximal humeral fractures with at least 5 year of follow up. Abstract: Background: Reverse shoulder arthroplasty (RSA) in complex shoulder fractures is ever more frequently. This study compares clinical and radiologic results of patients with comminuted proximal humeral fractures (PHFs) treated with RSA, with and without tuberosities grafting. Methods: Between January 2009 and June 2014, 55 patients aged ≥65 years with 3- and 4-part PHFs were treated surgically. Patients' files and the hospital's digital database were reviewed retrospectively with at least 5-year of follow up. We constituted three groups according to the tuberosity consolidation: patients in whom the tuberosities showed anatomic consolidation (Group I) and patients either with secondary displacement of the tuberosities (Group II) or without tuberosity repair (Group III). Results: The 74% of the repaired tuberosities consolidated in anatomic position. Among range of motion (ROM), we reported that forward elevation, abduction and external rotation were significantly better in Group I than those in Group II-III. Furthermore, quick Dash score and Constant score showed more satisfied results in Group I. Regarding complications, not infection or instability were found in group I. On the other hand, in group II, we reported one patient with deep infection, leading to two steps surgery. In group III, we recorded two patients with instability required implant revision and one with deep infection treated by revision. Conclusion: RSA showed satisfied results even at 5 year follow up. Preservation of the tuberosities in anatomic position improves active forward elevation and external rotation as well as patient satisfaction with less complications.